2019
DOI: 10.1111/jpi.12550
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin regulates the activities of ovary and delays the fertility decline in female animals via MT1/AMPK pathway

Abstract: Female fertility irreversibly declines with aging, and this is primarily associated with the decreased quality and quantity of oocytes. To evaluate whether a long‐term of melatonin treatment would improve the fertility of aged mice, different concentrations of melatonin (10−3, 10−5, 10−7 mol/L) were supplemented into drinking water. Melatonin treatments improved the litter sizes of mice at the age of 24 weeks. Mice treated with 10−5 mol/L melatonin had the largest litter size among other concentrations. At thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 69 publications
(144 reference statements)
1
72
0
Order By: Relevance
“…Some of the differentially expressed genes have functions relating to fertility through cellular signaling and regulation of the immune system ( PLCB1, PIK3R1, EPHA3 and CD109 ) or embryonic development ( TIAM1 and SYNE1 ). Others had functions relating to cellular adhesion ( ABLIM3, CADPS, MEG3, SDK2, STC1 and STX16 ), DNA binding and repair ( AHDC1 and POLD3 ) , cellular signaling events ( DCP1A, FNIP2, PIK3R1, PKHD1, PLCB1 and NTRK2 ) and metabolism ( FHIT ) [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Unfortunately, some of the differentially expressed candidate gene functions are still uncharacterized (CHD9, KIAA0825, MAP6, PRKG1, RAB3C, ROBO1, UPK1B and ZCCHC14) .…”
Section: Resultsmentioning
confidence: 99%
“…Some of the differentially expressed genes have functions relating to fertility through cellular signaling and regulation of the immune system ( PLCB1, PIK3R1, EPHA3 and CD109 ) or embryonic development ( TIAM1 and SYNE1 ). Others had functions relating to cellular adhesion ( ABLIM3, CADPS, MEG3, SDK2, STC1 and STX16 ), DNA binding and repair ( AHDC1 and POLD3 ) , cellular signaling events ( DCP1A, FNIP2, PIK3R1, PKHD1, PLCB1 and NTRK2 ) and metabolism ( FHIT ) [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Unfortunately, some of the differentially expressed candidate gene functions are still uncharacterized (CHD9, KIAA0825, MAP6, PRKG1, RAB3C, ROBO1, UPK1B and ZCCHC14) .…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have indicated that melatonin grants protective effects on ovarian follicles against the toxicity induced by gonadotoxic agents such as palmitic acid (PA), Di (2-Ethylhexyl) phthalate, and nicotine. [39][40][41][42] Melatonin's proposed protective benefits are based on documentation of inhibition of ER stress, reduction of reactive oxygen species (ROS) levels, and inhibition of apoptosis. Previous literature 26,27 indicated that melatonin significantly decreased the cisplatin-mediated phosphorylation of PTEN, AKT, and translocation of FOXO3a from the nucleus to cytoplasm in primordial oocytes, blocking the activation of primordial follicles in the mouse ovary.…”
Section: Discussionmentioning
confidence: 99%
“…In our work, we first confirmed the expression of melatonin receptor MT1 in both primary and immortalized microglia. MT1 is coupled to Gi and Gq proteins, and its activation inhibits the formation of cyclic AMP, activates AMP-activated protein kinase (AMPK) signaling, and inhibits phospho-CREB and protein-kinase A signaling [55][56][57]. This isoform, in particular, was here chosen because of its known involvement in the neuroprotective actions of melatonin, as from experimental models of newborn hypoxic-ischemic brain injury [17].…”
Section: Discussionmentioning
confidence: 99%